Análise da epidemiologia espaço-temporal dos casos e óbitos por sífilis congênita e seus fatores associados - Pinheiro, Yago Tavares (2024)
Introduction: Congenital syphilis (CS) is an infection caused by the bacterium Treponema Pallidum, the incidence of which has increased significantly in recent years in several low-, middle-, and high-income countries, becoming a health problem that requires strategies to improve the identification, treatment, and monitoring of potential cases and deaths caused by this disease. Objective: To analyze the spatiotemporal epidemiology of cases and deaths from CS in different regions of the world and identify possible factors that may influence this process. Methods: This is a mixed-methods study divided into four studies. Study 1: Systematic review protocol to analyze the incidence/prevalence of syphilis in pregnant women and CS in Brazilian cities and their respective predictors, structured according to the PRISMA recommendations; Study 2: Scoping review protocol based on the Joanna Briggs Institute guidelines and guided by PRISMA-ScR, to map the spatiotemporal distribution of CS in the world and the social determinants of health involved in this process. Study 3: Ecological study to describe the spatial distribution of deaths from CS in Brazil, conducted using aggregated secondary data available in Brazilian government information systems, corresponding to the 482 Immediate Urban Articulation Regions; Study 4: Scoping review developed based on the recommendations of the Joanna Briggs Institute and PRISMA-ScR to describe the dynamics of the spatial-temporal distribution of CS cases in different regions of the world and identify the social determinants of health that influence this process. Study 5: This is an ecological study that considered cases and deaths from CS in Brazil between 2008 and 2022. The incidence rate and the infant mortality rate from congenital syphilis were considered the dependent variables of the study. In addition, the independent variables of the study were: quantity and value approved for health promotion and prevention actions in primary care, number of prenatal consultations for pregnant women, and number of prenatal consultations for the partner. Linear regression for panel data was applied to predict the effect that independent variables have on dependent variables, considering each municipality as the unit of analysis and each year as the unit of time. All analyses considered a 95% confidence interval. Results: Studies 1 and 2 described the respective research questions, as well as the methodological procedures by which each study should be conducted, which included definition of databases, inclusion criteria for studies, and collection and analysis of the information found. In study 3, we observed that the mortality rate for CS was 0.64 deaths per 1,000 live births. The distribution of deaths occurred heterogeneously, with the highest rates in the states of Pará, Acre, Rondônia, Rio de Janeiro, and part of Amazonas. We identified statistically significant spatial clusters throughout the country, with clusters with a high-high pattern in Pará, Rio de Janeiro, and Mato Grosso (p<0.05). We observed that the Gini index (p=0.008; 95% CI: 0.02–0.11), the number of nurses in primary care (p=0.027; 95% CI: 0.0005–0.00003), and the proportion of non-treponemal tests per pregnant women (p=0.016; 95% CI: 0.005–0.001) are variables that influence the occurrence of deaths. In study 4, we identified that countries in the American continent (Brazil, the United States, and Colombia) showed a growing trend in CS cases in recent years, while regions in Asia, especially provinces in China, showed a reduction in cases. In addition, Brazilian studies presented divergent incidence rates for the same region and period analyzed. We note that the factors that determine the occurrence of CS in the territory are homogeneous, that is, regardless of the location or country, the spatio-temporal dynamics of the disease are determined by the following factors: per capita income, population density, education, illiteracy rate, human development index, migration rate, social vulnerability index, water supply, basic sanitation, prenatal care, percentage of low birth weight babies, occurrence of AIDS co-infection, coverage of the supplementary health system and scope of primary care. Finally, in study 5, it was identified that during the analyzed period, the incidence of CS varied between 1.98 and 10.33 cases/1,000 live births, while mortality in the same period varied between 1.87 and 8.08 deaths/100,000 live births. It was observed that the quantity (p<0.001) and value approved (p<0.001) for actions and the number of prenatal consultations for pregnant women (p=0.003) influenced the incidence of the disease. However, there was no significant effect on mortality. The number of prenatal consultations of the partner was not able to influence any of the dependent variables. Final considerations: Despite the reduction in cases of CS in some regions of the world, there are still places more vulnerable to the occurrence of this disease, and an analysis of sociodemographic, economic and assistance factors is important to define effective control strategies.